2012
DOI: 10.1088/0004-637x/761/2/121
|View full text |Cite
|
Sign up to set email alerts
|

Foretellings of Ragnarök: World-Engulfing Asymptotic Giants and the Inheritance of White Dwarfs

Abstract: The search for planets around White Dwarf stars, and evidence for dynamical instability around them in the form of atmospheric pollution and circumstellar discs, raises questions about the nature of planetary systems that can survive the vicissitudes of the Asymptotic Giant Branch (AGB). We study the competing effects, on planets at several AU from the star, of strong tidal forces arising from the star's large convective envelope, and of the planets' orbital expansion due to stellar mass loss. We, for the firs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
283
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(290 citation statements)
references
References 94 publications
6
283
1
Order By: Relevance
“…If, in contrast, the observations are the consequence of one or more asteroid-sized (∼1 km) bodies on nearly circular orbits, then a similar scenario as outlined before is unlikely to work because the asteroid would induce a tidal bulge on the white dwarf that is too small (e.g., consider a white dwarf-equivalent version of Equations (1)- (2) of Mustill & Villaver 2012) to circularize the orbit. The asteroid further would be too large to be circularized by radiation alone, either through the Yarkovsky effect or Poynting-Robertson drag (Veras et al 2015a(Veras et al , 2015c.…”
Section: Discussionmentioning
confidence: 99%
“…If, in contrast, the observations are the consequence of one or more asteroid-sized (∼1 km) bodies on nearly circular orbits, then a similar scenario as outlined before is unlikely to work because the asteroid would induce a tidal bulge on the white dwarf that is too small (e.g., consider a white dwarf-equivalent version of Equations (1)- (2) of Mustill & Villaver 2012) to circularize the orbit. The asteroid further would be too large to be circularized by radiation alone, either through the Yarkovsky effect or Poynting-Robertson drag (Veras et al 2015a(Veras et al , 2015c.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case with many CE simulations (e.g., Sandquist et al 1998;Passy et al 2012a) and may have some effect on the CE outcome (Iaconi et al, 2016, in preparation). However, in the case of planetary companions, it is likely that the effect of starting close to the surface is minimal: companions as far as 2-3 stellar radii are likely to be captured (Villaver & Livio 2009;Mustill & Villaver 2012), but the angular momentum of the orbit transferred to the primary would confer to it only a relatively minor surface velocity of 1.1 − 1.3 km s −1 for the AGB star and 3.2 − 3.9 km s −1 for the RGB star (this range was found assuming that all the orbital angular momentum of the planet at a distance of 2-3 stellar radii is transferred to the envelope of the giant, and that this envelope rotates rigidly), not too different from our non-rotating initial models. …”
Section: Methodsmentioning
confidence: 99%
“…Initially focusing on the future of the solar system (Sackmann et al 1993;Duncan & Lissauer 1998), a number of theoretical studies have shown that a fraction of planets can survive the red-giant stage Table 1 is available in electronic form at http://www.aanda.org of their host stars (Villaver & Livio 2007, 2009Nordhaus et al 2010;Mustill & Villaver 2012). The ensuing long-term orbital evolution is complex and may lead to planet ejections or collisions (Debes & Sigurdsson 2002;Veras et al 2011;Voyatzis et al 2013).…”
Section: Introductionmentioning
confidence: 99%